2005
DOI: 10.4049/jimmunol.174.2.983
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in IκBε and Changes in NF-κB Activity during B Lymphocyte Differentiation

Abstract: The levels and stability of IκBε have been examined in unstimulated and stimulated splenic B cells and compared with that of IκBα and IκBβ. Primary murine splenic B cells but not T cells were found to contain high levels of IκBε protein, equivalent to levels of the abundant IκBα. Most agents that activate IκBα and IκBβ degradation do not induce rapid degradation of IκBε. Interestingly, however, the levels of IκBε, but not of IκBα or IκBβ, are dramatically reduced upon the stimulation of B cells both in vivo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 63 publications
1
20
0
1
Order By: Relevance
“…IBε levels decreased more rapidly and more significantly than IB␤. Our data are consistent with previous results showing that IBε levels are reduced much more dramatically than IB␣ levels after B-cell stimulation with LPS for 24 h. However, it must be stressed that, in interleukin-4-activated B cells, IBε does not degrade as rapidly as IB␣ after LPS stimulation, thus suggesting that the stimulation of degradation of the different IB proteins not only depends on the stimulus but also exhibits cell activation stage specificity (11). It appears that the canonical and noncanonical NF-B pathways can be distinguished by their dependence on kinases that regulate the stimulus degradation of IB proteins IKK␤ and IKK␣, respectively (20,21).…”
Section: Discussionsupporting
confidence: 82%
“…IBε levels decreased more rapidly and more significantly than IB␤. Our data are consistent with previous results showing that IBε levels are reduced much more dramatically than IB␣ levels after B-cell stimulation with LPS for 24 h. However, it must be stressed that, in interleukin-4-activated B cells, IBε does not degrade as rapidly as IB␣ after LPS stimulation, thus suggesting that the stimulation of degradation of the different IB proteins not only depends on the stimulus but also exhibits cell activation stage specificity (11). It appears that the canonical and noncanonical NF-B pathways can be distinguished by their dependence on kinases that regulate the stimulus degradation of IB proteins IKK␤ and IKK␣, respectively (20,21).…”
Section: Discussionsupporting
confidence: 82%
“…NF-B is intimately involved in CSR by binding to the promoter of the immunoglobulin C␥1 gene (34) as well as by stimulating the expression of genes involved in CSR (35). The exact involvement of different NF-B and IB isoforms in CSR is still unknown (33). Our results can give some hints regarding this interesting phenomenon.…”
Section: Identification Of the Role Of Each Feedback Circuit In The Nmentioning
confidence: 74%
“…More recently, it has been observed that B cells lacking IkBe have augmented basal and B-cell receptor (BCR)-induced nuclear c-Rel (Clark et al 2011). IkBe is differentially expressed during B-cell development and has been proposed to regulate both p65-and c-Rel-containing NF-kB complexes in B cells (Doerre and Corley 1999;Doerre et al 2005). The temporal and cell type-specific degradation and expression of IkBe support the hypothesis that different IkBs play unique functions in NF-kB responses and indicate that a more detailed analysis of IkBe function in vivo is needed.…”
Section: Ikbe: Slow Startermentioning
confidence: 99%